2011
DOI: 10.1177/1352458511398885
|View full text |Cite
|
Sign up to set email alerts
|

Critical appraisal of animal models of multiple sclerosis

Abstract: Experimental autoimmune encephalomyelitis (EAE) is a spectrum of neurological disorders in laboratory animals that is used to model multiple sclerosis (MS). However, few agents have translated from efficacy in EAE to the treatment of human disease. Although this may reflect species differences in pathological disease mechanisms, importantly it may also relate to the practice of how drugs and models are currently used. This often bears very little resemblance to the clinical scenarios where treatments are inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
90
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 68 publications
(157 reference statements)
2
90
0
Order By: Relevance
“…This observation correlates with a clinical study which found that MS patients with Frontiers in Microbiology | Microbial Immunology positive H. pylori serology tests had lower disability scores than seronegative patients (Mohebi et al, 2013). Infiltration of leukocytes into the CNS has been shown to correlate with lesion load within the spinal cord of EAE mice (Baker et al, 2011). Those infected with H. pylori had markedly reduced numbers of Th1 and Th17 cells in both the CNS and spleen.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This observation correlates with a clinical study which found that MS patients with Frontiers in Microbiology | Microbial Immunology positive H. pylori serology tests had lower disability scores than seronegative patients (Mohebi et al, 2013). Infiltration of leukocytes into the CNS has been shown to correlate with lesion load within the spinal cord of EAE mice (Baker et al, 2011). Those infected with H. pylori had markedly reduced numbers of Th1 and Th17 cells in both the CNS and spleen.…”
Section: Discussionsupporting
confidence: 74%
“…MS is an inflammatory demyelinating immune-mediated disorder which affects the central nervous system (CNS). Development of autoreactive T cell responses against CNS-derived antigens leads to infiltration of Th1 and Th17 cells into the CNS (Goverman, 2009;Baker et al, 2011), resulting in damage to the myelin sheath of neural axons, inflammation, and neurodegeneration (Frohman et al, 2006). Studies have shown that the balance between pro-inflammatory Th1 and Th17 responses and anti-inflammatory Treg responses, either in terms of numbers or functional activity, are important in MS development and progression (Edstrom et al, 2011;Sellebjerg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous T cell directed therapies significantly reduce disease severity in this model [8,9], T cell depletion with anti-CD3 and anti-CD4 monoclonal antibodies failed in clinical trials for MS [10,11]. Depletion of peripheral B cells with anti-CD20 monoclonal antibodies in EAE enhances or inhibits disease severity dependent upon the time of dosing and the specific EAE model used.…”
Section: Introductionmentioning
confidence: 99%
“…One recent example that is highly relevant to neurology is the development of contemporary immunomodulatory treatments for multiple sclerosis based on preliminary studies in a CNS autoimmune disorder induced experimentally in animals. 4 Continuing identification of innovative therapies using animal models is anticipated in the future as a result of increasingly sophisticated molecular genetic, stem cell, and epigenetic research programs. 5 Animal research continues to be critical for protecting patients from premature approval of potentially deleterious drugs.…”
mentioning
confidence: 99%
“…8,10 Telephone and e-mail harassment, vandalism (broken windows, flooding), home invasion, and firebombing have all been documented as methods of intimidating scientists engaged in animal research. 4 In January 1990, the University of Tennessee received a letter from anti-animal research extremists threatening to assassinate a veterinary dean within 12 months. One month later, the dean of the veterinary school at the University of Tennessee died as a result of a gunshot wound received while on his private farm.…”
mentioning
confidence: 99%